Sod-Based Peanut/Cotton Rotation-Soil Health Part 1: Root Depth, Earthworms and Soil Water Infiltration - Tawainga W. Katsvairo; David L. Wright; James J. Marois; D. Hartzog; P. J. Wiatrak; Jimmy R. Rich (EDIS)
SS-AGR-124, a 4-page article by T. W. Katsvairo, D. L. Wright, J. J. Marois, D. Hartzog, P. J. Wiatrak and J. R. Rich, reports on the importance of perennial grasses on soil health and focuses on root growth, earthworm population densities and soil water infiltration. Published by the UF Department of Agronomy, July 2006.